Relationship between Parent’s Knowledge, Attitude, and Practice of Oral Health Maintenance with Oral Hygiene of 7 to 9-year-old Students - Trihapyanti, Rizki A.; Samiaty, Asty; Wardani, Riana; Ernawaty, Ernawaty (e-GiGi, 2025)
Abstract: Childhood is the beginning of behavior formation; therefore, it is expected that parents can educate their children to behave properly to maintain oral health. This study aimed to evaluate the relationship between knowledge. attitude, and parental practice with the oral hygiene of children of 7-8 years. This was an analytical study with a cross-sectional design. Sampling was carried out using simple random sampling technique on parents and students aged 7-8 years at SD Banjarsari Bandung (elementary school). The study was conducted by using OHI-S examinations to students and giving questionnaires to their parents. The relationship between knowledge, attitude, and practice of parent’s oral health maintenance with oral hygiene of the students was analyzed using the Spearman rank correlation analysis. The results showed that the correlation value between parental knowledge and student oral hygiene was 0.918 (>0.05), meanwhile the correlation value between parental attitude and student oral hygiene was 0.379 (>0.05), and the correlation value between parental practice and student oral hygiene was 0.419 (>0.05). All of the correlation values showed no significant relationships. In conclusion, there is no relationship between parent’s knowledge, attitude, and practice of oral health maintenance with oral hygiene of students aged 7-8 years. Keywords: parents; oral hygiene; students of elementary school